Towards trade facilitation via regulatory convergence: An analysis of the TTIP chapter on Electronic Communications - Markus Fredebeul-Krein (International Telecommunications Society (ITS), 2016)
To give the exchange of goods and services between the European Union (EU) and the United States (U.S.) new momentum the two parties are currently negotiating the transatlantic free trade agreement Transatlantic Trade and Investment Partnership (TTIP). The aim is to create the largest free trade area in the world. The agreement, once entered into force, will oblige EU countries and the U.S. to further liberalize their markets. The negotiations on TTIP include a chapter on Electronic Communications/ Telecommunications. The challenge therein will be securing commitments for market access to Electronic Communications services. At the same time, these commitments must reflect the legitimate need for consumer protection issues. The need to reduce Electronic Communications-related non-tariff barriers to trade between the Parties is due to the fact that these markets are heavily regulated. Without transnational rules as to regulations national governments can abuse these regulations to deter the market entry by new (foreign) suppliers. Thus the free trade agreement TTIP affects in many respects regulatory provisions on and access to Electronic Communications markets. The objective of this paper is therefore to examine to what extend the regulatory principles for Electronic Communications markets envisaged under TTIP will result in trade facilitation and regulatory convergence between the EU and the U.S. As to this question the result of the analysis is that the chapter on Electronic Communications will be an important step towards facilitating trade in Electronic Communications services. At the same time some regulatory convergence will take place, but this convergence will not lead to a (full) harmonization of regulations. Rather the norm, also after TTIP negotiations will have been concluded successfully, will be mutual recognition of different regulatory regimes. Different regulations being the optimal policy response in different market settings will continue to exist. Moreover, it is very unlikely that such regulatory principles for the Electronic Communications sector are a vehicle for a race to the bottom in levels of consumer protection.
Keywords: 330; regulation; liberalisation; electronic communications markets; TTIP